One-step fabrication of all-in-one flexible nanofibrous lithium-ion battery. (15th August 2023) - Akhmetova, Kamila; Tatykayev, Batukhan; Kalybekkyzy, Sandugash; Sultanov, Fail; Bakenov, Zhumabay; Mentbayeva, Almagul
Abstract: Herein was proposed a facile and beneficial strategy to solve "hot" issues of existing flexible batteries by providing a uniform and stable framework for bendable, portable and semi-transparent "all-in-one" lithium-ion batteries (LIBs). The "all-in-one" flexible LIB was fabricated by one-stage electrospinning of PVDF-HFP-based precursor solution loaded with active materials. Nanostructured graphite and LiFePO4 were used as anode and cathode active materials, respectively. An optimum amount of CNT was added to the electrospinning solutions to increase the electronic conductivity of the fibrous electrodes. The electrochemical performance of the anode and cathode membranes was investigated in lithium half cells. The areal capacities of the electrodes were around 5 μAh cm −2 with stable performance for >30 cycles. Further, three solutions for the anode, separator (containing polymer only) and cathode were electrospun successively on top of each other. As a result, a flexible, bendable and semi-transparent membrane containing all three components (i.e., cathode, separator and anode) was fabricated. The membrane was then soaked into the liquid electrolyte (LiPF6 in EC/DMC/DEC (1:1:1 vol%)) and assembled into a quasi-dry full-cell battery. As a result, the potential of the "all-in-one" flexible battery was stable even after 40 bends. Graphical abstract: Unlabelled Image Highlights: All-in-one flexible lithium-ion battery was fabricated by one-stage electrospinning. The nano-sized graphite and LiFePO4 /C were incorporated into nanofibers. CNTs inside nanofibers act as conductive bridges between electrode nanoparticles. Electrospun solo membrane provided a framework for bendable and semitransparent LIB.